Capitalism, territory and conflict: an interview with Maritza Paredes and Anke Kaulard - Guevara Bustamante, Andrea (2024)
The following interviews aim to present this year’s theme, “Crisis and Futures of Capitalism: Power, Technology, and Environment.” For this purpose, we spoke with researchers Maritza Paredes and Anke Kaulard. Throughout the interview, key concepts were discussed to understand the environmental issues in current capitalism, such as the notions of “territory,” “territorial conflict,” and “climate justice.” In this approach, the need to understand the territory holistically is emphasized as a social and symbolic production, that is both contested and negotiated by various actors and in which meaning, interdependence with nature, historical processes, social practices, and power relations are inscribed. Additionally, the limitations of how the state is structured to address these conflicts are discussed. Similarly, attention is drawn to the various responses communities undertake in the face of the reconfiguration and attempt to control their territories within the framework of contemporary capitalism.